2019
DOI: 10.1016/j.sjbs.2018.12.006
|View full text |Cite
|
Sign up to set email alerts
|

The antioxidant rich active principles of Clerodendrum sp. controls haloalkane xenobiotic induced hepatic damage in murine model

Abstract: Clerodendrum is a plant with potent antioxidant activity and has been frequently employed as a traditional remedy against bronchitis, asthma, liver and stomach disorders. Three species of genus Clerodendrum namely Clerodendrum indicum, C. colebrookianum and C. inerme (Syn. Volkameria inermis) were investigated for their possible activity against oxidative stress induced liver injury. Apart from generation of Reactive Oxygen Species (ROS) in the WRL-68 cell line (human hepatic cell line), in-vitro and in-vivo a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Notably, basal ROS levels were unaffected by treatment with different fractions (100 μg/mL) of C. glandulosum extract alone ( Figure S2 in Supporting Information ). In an earlier study, C. glandulosum leaf extract showed marked protection against H 2 O 2 ‐induced oxidative insult in human hepatocyte cell lines [12] . Other studies reported that extract obtained from C. glandulosum leaf successfully restored the endogenous antioxidant status depleted during chemical as well as high‐calorie induced oxidative stress in an animal model [11,13] .…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Notably, basal ROS levels were unaffected by treatment with different fractions (100 μg/mL) of C. glandulosum extract alone ( Figure S2 in Supporting Information ). In an earlier study, C. glandulosum leaf extract showed marked protection against H 2 O 2 ‐induced oxidative insult in human hepatocyte cell lines [12] . Other studies reported that extract obtained from C. glandulosum leaf successfully restored the endogenous antioxidant status depleted during chemical as well as high‐calorie induced oxidative stress in an animal model [11,13] .…”
Section: Resultsmentioning
confidence: 92%
“…In an earlier study, C. glandulosum leaf extract showed marked protection against H 2 O 2 -induced oxidative insult in human hepatocyte cell lines. [12] Other studies reported that extract obtained from C. glandulosum leaf successfully restored the endogenous antioxidant status depleted during chemical as well as high-calorie induced oxidative stress in an animal model. [11,13] Our results corroborated with these previous reports that bioactive fractions of C. glandulosum rich in phenolic and flavonoids could inhibit ROS production effectively.…”
Section: Cytoprotective Effect and Inhibition Of Ros Productionmentioning
confidence: 97%
See 1 more Smart Citation
“…A total of four in-vitro free radical scavenging activity namely DPPH, hydroxyl radical, nitric oxide and hydrogen peroxide as well as phenol and flavonoid content were evaluated to study the efficacy of CSL [12].…”
Section: In-vitro Antioxidant Assaysmentioning
confidence: 99%
“…A total of eight antioxidant assays were performed by previously reported methods using silver Nano, rajatbhasma nanoparticle and plant extract (Dutta et al, 2018;Kar et al, 2019).…”
Section: Determination Of In-vitro Antioxidant Activitymentioning
confidence: 99%